The Stockholm syndicate - Forbes, Colin (London : Pan Books, 1996)
Jules Beaurain, ex-chief of the anti-terrorist squad in Brussels, with his assistant Louise Hamilton, uses a secret force to fight the menace and battle against the powers of evil which are holding governments and international institutions in the West to ransom.
National College of Business and Arts
Keywords: International business enterprises -- Fiction; Political fiction